Effects of concurrent strenght and endurance training sequence order on physical fitness performance in adolescent students - Costa, A. M. (2018)
The aim of the study was to examine the effect of the sequence order of concurrent training on physical performance in students. 31 subjects were recruited from a Portuguese public high school and were randomly divided in strength training followed by endurance exercise group (GSE, n=12) and endurance followed by strength training group (GAS, n=11). The training program was performed during physical education classes, 2 times per week during 10 weeks. Anthropometrics and physical variables were assessed before (M1), after 5 weeks of training (M2) and after the training period (M3). Training‐induced significant differences in both groups after the training program [1kg and 3kg medicine ball throw gains (GES: 4.6 to 6.3%, and 3.9 to 6.0%, GSE: 5.0 to 9.3% and 3.0 to 8.4%), VO2max (GES: 2.3 to 3.7%, GSE: 2.8 to 8.0%), push-ups (GES: 11.7 to 12.5%; GSE: 13.3 to 23.5%), standing long jump (GES: 5.1 to 4.3%, GSE: 2.9 to 5.3%), counter movement jump (GES: 5.1 to 4.3%, GES: 3.1 to 8.1%) and sprint running 20m (GES: -1.5 to -1.2%, GSE: -1.0 to -1.7%). Independently of the sequence order, concurrent training appear to change body composition and increase physical fitness in students during physical education classes.